2019
DOI: 10.3389/fonc.2019.00693
|View full text |Cite
|
Sign up to set email alerts
|

A Robust 8-Gene Prognostic Signature for Early-Stage Non-small Cell Lung Cancer

Abstract: Background: The current staging system is imprecise for prognostic prediction of early-stage non–small cell lung cancer (NSCLC). This study aimed to develop a robust prognostic signature for early-stage NSCLC, allowing classification of patients with a high risk of poor outcome and specific treatment decision. Method: In the present study, a comprehensive genome-wide profiling analysis was conducted using a retrospective pool of early-stage NSCLC patient data from the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 50 publications
0
61
1
Order By: Relevance
“…Zhang et al found that dissection of the 4th lymph nodes was related to a better prognosis, although this was not recommended by the International Association for the Study of Lung Cancer (IASLC) [32]. There are also scholars who believe that the present staging guide is insufficient for predicting individual-level overall survival because many early-stage patients may experience a later relapse [33,34]. Moreover, Valeria et al suggested abandoning the concept of non-small cell lung cancer because a large body of experimental evidence suggests that LUAD and lung squamous cell carcinoma appear to be distinct tumours at the molecular, pathological and clinical levels [35].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that dissection of the 4th lymph nodes was related to a better prognosis, although this was not recommended by the International Association for the Study of Lung Cancer (IASLC) [32]. There are also scholars who believe that the present staging guide is insufficient for predicting individual-level overall survival because many early-stage patients may experience a later relapse [33,34]. Moreover, Valeria et al suggested abandoning the concept of non-small cell lung cancer because a large body of experimental evidence suggests that LUAD and lung squamous cell carcinoma appear to be distinct tumours at the molecular, pathological and clinical levels [35].…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast, a prognostic signature may offer insights into the course of a disease, the prediction of survival rates and the response to a specific treatment. 10,11 As far as NSCLC is concerned, many diagnostic signatures [12][13][14][15] and prognostic signatures [16][17][18][19][20] have been identified. For example, a recent study used 183 AC and 80 SCC patients as a training set and obtained a 42-gene signature to discriminate these two subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…identi ed a 7-lncRNA signature for predicting the OS of patients with NSCLC after combining lncRNA pro les from 4 GEO datasets and validated the signature in 2 independent datasets (TCGA and GSE31210). Recently, He et al [32] proposed a novel 8-gene signature as a prognostic indicator for patients with early-stage NSCLC after analyzing data from the GEO and TCGA projects. However, the abovementioned prognostic signatures generated by data mining have not been con rmed in patients with NSCLC in a prospective multicenter study.…”
Section: Discussionmentioning
confidence: 99%